The power of spirituality in symptomatic and functional outcomes of patients with major depressive disorder in an Egyptian sample - Elgohary Sallam, Eman (Journal of spirituality in mental health, 2023)
Assessing the role of spirituality on outcomes in Arab patients with major depressive episode and the possible confounding factors is lacking. The aim of the present study was to determine whether spirituality was associated with symptomatic and functional outcomes in an outpatient facility. A total of 79 participants were consecutively enrolled in this study who presented to a psychiatry outpatient clinic over the course of two years. Baseline and follow-up variables were collected via direct interviews of the patients and their caregivers. In order to assess symptomatic outcome, Hamilton Depression Rating Scale (HAMD) is used monthly over 6 months and its percent of reduction is used as an indicator for symptomatic outcome, functional outcome was measured by the percentage of reduction of both scales (WHO Disability Assessment Schedule (WHODASII) and WHO Quality of Life instrument (WHOQOL-100)) that were administrated twice at baseline interview then after 6 months of follow-up (final interview), while spirituality of the sample was measured by using Daily Spiritual Experience Scale (DSES) which assess the intrinsic Spirituality, it is a 16-item self-report measure designed to assess ordinary experiences of connection with the transcendent in daily life. Spirituality was significantly correlated to the disability scale percentage reduction (p = .003), while no significant relation between Spirituality with symptomatic outcome nor the quality of life aspect of functional outcome (p = .259) and (p = .134), respectively. Demonstrating a relationship between spirituality and functional outcome would suggest a new therapeutic route of improving interventions designed to increase outcome and improve quality of life and functioning for Arab patients with major depression.